Does ischaemic preconditioning improve exercise performance? - Cocking, S. (ASPETAR Sports Medicine Journal, 2016)
As ischaemic preconditioning continues to show promise in the laboratory environment, more organisations may look to employ it in applied performance settings. However, there are some key questions that are yet to be answered including: